Devonian trilobites from the Amazonas Basin: systematic diversity, taphonomy, and biogeographic significance - Carvalho, Maria da Gloria Pires de; Ponciano, Luiza Corral Martins de Oliveira (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2015)
Although the Devonian invertebrate biota of the Amazonas Basin is incompletely known, its unusual mixture of supposedly Malvinokaffric and Appalachian taxa is of considerable biogeographical interest. The history of research on Devonian trilobites from the Amazonas Basin is summarized. These fossils occur in the Maecuru (latest Emsian – early Eifelian) and Ererê (latest Eifelian – early Givetian) formations, representing the families Homalonotidae, Dalmanitidae, and Calmoniidae. Trilobite diversity is higher in the Maecuru (nine named plus six indeterminate taxa) than the Ererê Formation (with only two named taxa), which displays faunal impoverishment generally. None of the Devonian Amazonas Basin trilobite species is known from other Malvinokaffric sites, suggesting very high endemicity within this basin. A taxonomic revision of “Homalonotus” derbyi (Clarke, 1890) is presented and a lectotype is designated. A lectotype and paralectotype are also designated for Eldredgeia paituna (Hartt & Rathbun, 1875). Some taphonomic observations of fossils from the Maecuru Formation are made, and a brief biogeographic synopsis of the Devonian Amazonas biota is also given.